ANALYSIS OF ANTIBIOTIC COST IN BROILER MANAGEMENT PRACTICE IN SUBANG REGENCY, WEST JAVA, INDONESIA - Sugiyono; Sabdoningrum, Emy Koestanti; Hidanah, Sri; Lokapirnasari, Widya Paramita; Luqman, Epy Muhammad; Hestianah, Eka Pramyrtha (Jurnal Biosains Pascasarjana, 2025)
Broiler farms are generally susceptible to disease attacks caused by viruses, bacteria, parasites, fungi, the environment, and deficiencies in nutritional elements. The use of antibiotics in the livestock industry generally aims to treat livestock so as to reduce the risk of death and restore livestock to a healthy condition. There are three patterns for rearing broiler chickens in Indonesia, especially in West Java, namely modern rearing using a closed house system, semi closed house and conventional rearing using open house system. This study aims to prove the analysis of the cost of antibiotics and their market potential needs to be known so that rational and balanced use of antibiotics can be illustrated with the benefits to the results of raising broiler livestock. The design used in this research was a purposive sampling. The variables in this research are the closed house, semi closed house and open house broiler farming systems. The independent variables in this research are the cost of antibiotics each bird per period. Descriptive analysis is used to obtain stewardship antibiotics based on the existing medication program. The antibiotic cost each bird per period from closed house amount is Rp. 70,49 + 38,65, semi closed house is Rp. 100,20 + 42,28, and open house is Rp. 130,32 + 64,68. The means of antibiotic cost each birds per period amount is Rp. 100,34 + 54,17 use a factor for forecasting market potency of antibiotic. The market potency per year in Subang regency amount Rp. 5.799.005.710 + 3.130.677.091, West Java Province amount Rp. 74.165.707.957 + 40.039.429.938, Indonesia amount Rp. 312.461.530.889 + 168.686.875.905. Apart from that, antibiotic stewardship on a broiler farm scale is also needed to get an idea regarding the appropriate use of antibiotics in broiler farms, especially in the Subang district area of West Java Province.